Controlled Release Of A poorly Water - Soluble Drug From An Amphiphilic And Ph - Sensitive Chitosan - Based Hydrogel - HOSSEIN HOSSEINZADEH (International Journal of Pharma and Bio Sciences, 2011)
The present work focused on the design of drug delivery system based on an amphiphilic and pH-sensitive hydrogel. The hydrogels were prepared via graft copolymerization of acrylic acid (AA) onto chitosan backbones by a free radical polymerization technique. The structure and surface morphology of the hydrogels were characterized by FTIR and SEM, respectively. The swelling and pH-sensitive properties of the hydrogels were also investigated. Due to the reversible swelling behavior of the hydrogels, the synthesized networks can sense the environmental pH change and achieve an oscillatory release pattern. Using drug theophylline as a model molecule, loading and the in vitro controlled drug-release behaviors of these hydrogels were investigated. The loading yield was found to mainly depend on the crosslinker amount. The results also indicate that the main parameter affecting the drug-release behavior of hydrogels is the pH of the solution. The release rate of theophylline from hydrogel at pH 7.4 was faster than that at pH 1.2 due to the shrinkage of the hydrogel at pH 1.2.